Freemasonry in America - Ortega Auquilla, Diego Patricio
In this thesis the arrival of Freemasonry in America, as well as the Masonic contribution and influence upon important events in the history of the United States were investigated. Further aims were to discuss the organizational structure of the Masonic family, the American Rites, and the functions of the lodge room. Finally, Freemasonry?s significant role within American society, the Masonic foundation in the organization of American institutions and Freemasonry?s charitable work were examined, as well. Both historical and quantitative methods were applied. The former provided the beginnings, growth and expansion of Freemasonry, and it revealed facts and relevant events through a study of the historical course of the influence, participation and contribution of Freemasonry within American society. The latter offered a rich, in-depth description of the Masonic activity over the course of U.S. history. The results of the study revealed that Freemasonry actively participated in the building of social life, culture and history, becoming the cornerstone of U.S. society. Freemasonry as a fraternal order and a voluntary organization reached the top of social prestige and popularity?s institutional structure proved to be unique due to the complexity and beauty of its ceremonies, tools, degrees, rites and lodges. In conclusion, Freemasonry?s contribution to the organization of U.S. social life, culture and government, the Masonic heritage within countless of American organizations and its service efforts and philanthropic work for the good of the mankind constituted clear evidence of Freemasonry?s central role upon the development of U.S. history and the improvement of American communities.